2005
DOI: 10.1073/pnas.0409873102
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB activation and potentiation of proinflammatory responses by theHelicobacter pyloriCagA protein

Abstract: The Helicobacter pylori immunodominant protein, CagA, is associated with severe gastritis and carcinoma. Injection of CagA into gastric epithelial cells by type IV secretion leads to actin-cytoskeletal rearrangements and cell scattering. CagA has been reported to have no role in the induction of transcription factor NF-B and IL-8, which are crucial determinants for chronic inflammation. Here, we provide several lines of evidence showing that CagA is able to induce IL-8 in a time-and strain-dependent manner. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
458
4
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 458 publications
(494 citation statements)
references
References 39 publications
13
458
4
7
Order By: Relevance
“…Intracellular CagA undergoes Src-dependent tyrosine phosphorylation and activates a eukaryotic phosphatase, leading to dephosphorylation of host cell proteins and cellular morphological changes (Backert et al, 2000;Higashi et al, 2002;Selbach et al, 2002;Stein et al, 2002). Recently, CagA has been shown to activate ␤-catenin and induce NF-B-mediated interleukin-8 release from gastric epithelial cells (Brandt et al, 2005;Franco et al, 2005). The presence of the cag island also influences the topography of colonization in the stomach, because H. pylori cag Ϫ strains predominate within the mucus gel layer, whereas cag ϩ strains are found immediately adjacent to epithelial cells (Camorlinga-Ponce et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular CagA undergoes Src-dependent tyrosine phosphorylation and activates a eukaryotic phosphatase, leading to dephosphorylation of host cell proteins and cellular morphological changes (Backert et al, 2000;Higashi et al, 2002;Selbach et al, 2002;Stein et al, 2002). Recently, CagA has been shown to activate ␤-catenin and induce NF-B-mediated interleukin-8 release from gastric epithelial cells (Brandt et al, 2005;Franco et al, 2005). The presence of the cag island also influences the topography of colonization in the stomach, because H. pylori cag Ϫ strains predominate within the mucus gel layer, whereas cag ϩ strains are found immediately adjacent to epithelial cells (Camorlinga-Ponce et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The cagA is reported to be found in more than half of the H. pylori isolates. It is known that cagA is a marker for the cag pathogenicity island and is associated with increased IL-8 production, nuclear factor-kB activation, mucosal inflammation and development of peptic ulcers, atrophic gastritis, and gastric cancer (6). The vacA gene encodes an 87-93 kDa molecular weight VacA protein, which induces cytoplasmic vacuoles in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, CagA also disturbs cell functions in a tyrosine phosphorylation-independent manner, activating a nuclear factor that induces transcription of several inflammatory genes (11). Furthermore, CagA is also capable of activating NF-κβ, which in turn induces interleukin-8 expression (12) and more recently, it has been reported that this bacterial protein deregulate the β-catenin signaling (13).…”
mentioning
confidence: 99%